2016
DOI: 10.1136/bmjsem-2015-000100
|View full text |Cite
|
Sign up to set email alerts
|

Low fitness, low body mass and prior injury predict injury risk during military recruit training: a prospective cohort study in the British Army

Abstract: BackgroundInjuries sustained by military recruits during initial training impede training progression and military readiness while increasing financial costs. This study investigated training-related injuries and injury risk factors among British Army infantry recruits.MethodsRecruits starting infantry training at the British Army Infantry Training Centre between September 2008 and March 2010 were eligible to take part. Information regarding lifestyle behaviours and injury history was collected using the Milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 28 publications
13
91
3
4
Order By: Relevance
“…The observed regimental injury pattern in terms of onset and anatomical location is similar to previous investigations within both military [1,5,7,9] and sporting populations [34]. Overuse injury is the most common for all CIC regiments, a characteristic observed in numerous other studies [1,5,8,9,15].…”
Section: Injury Typesupporting
confidence: 85%
See 4 more Smart Citations
“…The observed regimental injury pattern in terms of onset and anatomical location is similar to previous investigations within both military [1,5,7,9] and sporting populations [34]. Overuse injury is the most common for all CIC regiments, a characteristic observed in numerous other studies [1,5,8,9,15].…”
Section: Injury Typesupporting
confidence: 85%
“…The Gurkha regiment reports the lowest four year average injury rate (21.67%) whilst the Parachute Regiment reports the highest (66.21%). A Study by Sharma, et al [1] Previously reported an overall injury incidence of 48.6% in all British infantry recruits based on 2006-2008 data, whilst another study [5] in the same institution, based on 2009-2011 data, found an even higher injury incidence of 58%. However, although revealing, these studies did not investigate individual regimental specific injury incidence.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations